Design Prototype Robot Vacuum Cleaner Based on Arduino Microcontroller with Autonomic Mode - Herdiansya Herdiansya; Yonky Pernando (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The development of robotics technology in the current era has become a highly relevant need to assist humans in various everyday activities. One significant application of this technology is the creation of a prototype